Sistema de armazenagem automatizado - Freitas, Juliane Aline de (2015)
The use of automated processes is becoming increasingly common in industries in order to reduce costs and increase productivity. In this course conclusion work automation of a storage system prototype was performed. A mechanical structure was developed, and a warehouse with eight positions, a robot with linear motion in three axes, an electronic structure, used with programmable logic controller S7-200 from Siemens, and supervision Elipse SCADA. The operator identifies the code through a camera and records in the supervisory system. Then, the charge operation is performed automatically. The flushing operation is also performed in an automated way when requested by the operator. In the operation screen you can view the pieces with their respective codes. With the installation of this system companies can achieve productivity gains, reduced storage area with increased floor space, reducing the run time, increased reliability of parts in stock.